The Copyright Infringement In Cinematography - Putri Andini (Journal of Law and Policy Transformation, 2018)
The drama entitled “Kau Yang Berasal Dari Bintang” produced by SinemArt and aired by RCTI TV station on 28 April 2014 was claimed as a plagiarism of the most popular South Korean drama "You Who Came from the Stars". Consequently, the screening of the drama was pending until the negotiation of the Korean and Indonesian production house was settled. This research advanced a question whether the Indonesian Copyright Law provides sufficient protection to the works of cinematography either produced by Indonesian or foreign nationals. To answer this research question, the legal protection theory of Phillipus M. Hadjon was used as a platform. It also analyzed the effective implementation of the Law by adopting the Effectiveness of Law Theory of Satjipto Rahardjo. Furthermore, it reviewed the settlement made by the Indonesian and South Korean production house. In order to obtain concrete findings, this research adopted a normative research method (doctrinal method) by using secondary data as its sources. Data collected were analyzed based on its content (a content analysis) by using the qualitative approach. The research found that cinematographic work is one of the protected works under the Indonesia Copyright Law; therefore the Indonesian drama violated the Law because of the similarities of stories, plot, and roles played with the Korean drama. However, the Law was not effective in its implementation due to its weak enforcement by those responsible and a lack of public awareness. It was also found that the amicable settlement through negotiations were the best solution to resolve the infringement of Copyright Law relating to cinematography.